2018
DOI: 10.1111/jcmm.13759
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain amino acids promote endothelial dysfunction through increased reactive oxygen species generation and inflammation

Abstract: Branched‐chain amino acids (BCAA: leucine, isoleucine and valine) are essential amino acids implicated in glucose metabolism and maintenance of correct brain function. Elevated BCAA levels can promote an inflammatory response in peripheral blood mononuclear cells. However, there are no studies analysing the direct effects of BCAA on endothelial cells (ECs) and its possible modulation of vascular function. In vitro and ex vivo studies were performed in human ECs and aorta from male C57BL/6J mice, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 56 publications
(129 reference statements)
1
85
1
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ signature found in women could be at least partially linked to this difference in BMI. Elevated concentrations of branched amino acids are known to promote endothelial dysfunction, inflammation, and oxidative stress 57 and may promote hypertension 58 . Insulin resistance could contribute to hypertension through altered NO release 59 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ signature found in women could be at least partially linked to this difference in BMI. Elevated concentrations of branched amino acids are known to promote endothelial dysfunction, inflammation, and oxidative stress 57 and may promote hypertension 58 . Insulin resistance could contribute to hypertension through altered NO release 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, taurine, which has anti-oxidant properties, can down-regulate the production of pro-in ammatory cytokines such as TNF-α, and also protect OBs against oxidative damage via Wnt/β-catenin-mediated activation of the extracellular regulated protein kinase (ERK) signaling pathway [37]. Additionally, elevation of branched-chain amino acids (BCAA: leucine, isoleucine and valine) can cause in ammation and oxidative stress in endothelial cells, thereby facilitating in ammatory cell adhesion and endothelial dysfunction [38]. On the other hand, metabolism of some amino acids can also regulate bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids are not only essential substances of proteins, but also as signal molecules regulate various physiological functions of the organism, such as precursors of many neurotransmitters and hormones, and intermediates of TCA circulation and glyconeogenesis [ 59 ]. Previous reports have demonstrated that branched-chain amino acids can increase the expression of eNOS and nitrotyrosine, and induce inflammatory response by activating the transcription factor NF-κB in endothelial cells [ 60 ]. Four potential biomarkers related to amino acid metabolism, including l -alanine, Ser-Lys-Lys-Ile, diaminomethylidene- l -ornithine, and Arg-Met-Arg-Thr, have been shown in Table 1 .…”
Section: Discussionmentioning
confidence: 99%